SWCC from grain size distribution curve - Lin, Alvin Yihui. (2009)
Although soil-water characteristic curve (SWCC) is of great importance in present day agricultural, soil science, geotechnical and geo-environmental engineering, it is not a readily available soil property. The main reason is that its measurement is expensive, time consuming and labour intensive. Therefore, models have been developed to predict the SWCC from more easily measurable and more readily available soil properties like particle-size distribution, organic matter content and dry density. These models are referred to as pedotransfer functions. The objective of the project is to evaluate pedotransfer functions for determining SWCC from grain size distribution curve using a database of grain size distribution curves and SWCCs. Two widely used pedotransfer functions, Gupta and Larson (1979) and Rawls et al. (1982), for estimating the SWCCs are evaluated and modified.